2023
DOI: 10.1101/2023.05.31.543180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interactions Between the Histone Variant H2Av and the Suppressor of Hairy wing Insulator Influence the DNA Damage Response and Lymph Gland Development inDrosophila

Abstract: Genome architecture is regulated by chromatin insulator proteins, and misregulation of insulator function is associated with genome instability and transcriptional regulatory defects in both vertebrates and Drosophila. Indeed, mutations of the sole insulator protein in humans, CTCF, are carcinogenic and mutations in the Drosophila insulator protein Suppressor of Hairy wing [Su(Hw)] lead to chromosomal rearrangements. However, the mechanism that links the DNA damage response and the regulation of transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Caspase/CAD causes DNA breaks around chromatin-modifying CCCTC-binding factor (CTCF) sites (chromatin insulators) to control gene expression by directly acting on a promoter or influencing promoter-enhancer interactions [108][109][110] . A study showed that the enrichment of insulator proteins at insulator sites rises after DNA damage by regulating H2Av in Drosophila 111 . Moreover, mammalian macrophage functions require a set of transcriptional regulators accomplished by the tissue microenvironment in the tissue-specific macrophage chromatin landscape 5,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase/CAD causes DNA breaks around chromatin-modifying CCCTC-binding factor (CTCF) sites (chromatin insulators) to control gene expression by directly acting on a promoter or influencing promoter-enhancer interactions [108][109][110] . A study showed that the enrichment of insulator proteins at insulator sites rises after DNA damage by regulating H2Av in Drosophila 111 . Moreover, mammalian macrophage functions require a set of transcriptional regulators accomplished by the tissue microenvironment in the tissue-specific macrophage chromatin landscape 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…All stocks were maintained at room temperature or 18°C, and genetic crosses using the GAL4/UAS system were maintained at 29°C on a 12 h light/ 12 h dark cycle. The following Drosophila stocks were used for this study: CHIZ-GAL4 UAS-mCD8::GFP 39 , Hml Δ -Gal4 UAS-2xEGFP, dome MESO -Gal4 UAS-2xEGFP, Nup98-GFP, w 111 8 , UAS-RedStinger (BL8546), and UAS-GTRACE LTO (BL28282) were from Utpal Banerjee’s lab. The following fly lines were obtained from Bloomington Drosophila Stock Center (BDSC): UAS-Akt RNAi (BL33615 and BL31701), UAS-Ask1 RNAi (BL35331 and BL32464), UAS-Drep1 RNAi (BL65944), UAS-Drep4 RNAi (BL67883), UAS-InR RNAi (BL31037), UAS-GC3Ai (BL84346), srp-mCherry (BL78361) 89 , DnaseII lo (BL1042), Dronc-DBS (BL83129), Ubi-p63-(FRT-STOP-FRT Stinger ) (BL32250), L-Caspase (BL92353) 53 , LexAop-Flp (BL55820), PCNA-GFP (BL25749), UAS-Apoliner (BL32121 and BL32123), EndoG MB07150 (BL26072), Drpr-GFP (BL63184), UAS-PI3K DN (BL8288), UAS-PI3K CAAX (BL25908), UAS-GFP-mCherry-Atg8a (BL37749) , UAS-Atg8a-GFP (BL51656), UAS-mCherry-Atg8a (BL37750), UAS-lexAop-2xmRFP (BL29956), UAS-p35 (BL5072), CasExpress mutant (BL65419), CasExpress (BL65420) 47 , UAS-mCD8::RFP (BL27398), Drep4-Gal4 (BL80624) 77 , UAS-FUCCI (BL55121), Cg-Gal4 (BL7011).…”
Section: Methodsmentioning
confidence: 99%